MENINGKATKAN KESADARAN PAJAK UMKM MELALUI PENDAMPINGAN PELAPORAN PAJAK SEDERHANA DI KOTA MATARAM - R. Ayu Ida Aryani; Ikang Murapi; Ni Ketut Sriwinarti; Muliani Muliani; Arie Cahyani; Layali Ihyani; Nukman Nukman (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The tax awareness of Micro, Small, and Medium Enterprises (MSMEs) in Mataram City still faces various obstacles, especially related to the understanding of tax obligations and the ability to prepare tax reporting independently. This condition causes some MSME actors to not carry out their tax obligations optimally. This community service activity aims to increase MSME tax awareness through simple tax reporting assistance tailored to the business characteristics of the participants. The implementation method includes tax socialization, training in the preparation of simple financial statements as a basis for tax reporting, tax calculation simulations, and direct assistance in the use of tax reporting applications. The activity was carried out in a participatory manner by involving MSME actors as the main subject of learning. The results of the activity showed that there was an increase in participants' understanding of tax functions, types of tax obligations, tax calculation procedures, and correct tax reporting procedures. Participants who previously had difficulties in compiling supporting documents for tax reporting began to be able to identify business transactions, compile simple records, and simulate tax reporting independently. In addition, this activity encourages the growth of awareness that tax compliance is an important part of business sustainability and contribution to regional development. The assistance provided not only increases the technical capacity of participants, but also builds a positive attitude towards tax compliance. Thus, this program makes a real contribution to strengthening the culture of tax awareness among MSMEs in Mataram City through an educational, applicative, and sustainable approach.